The Strawberry Shortcake movie sky's the limit - Cummer, Anna.; Ball, Ashleigh, 1984-; Nilson, Ingrid; Jaud, Janyse; McKillip, Britt, 1991-; Libman, Andrea, 1984-; Saunig, Ashley; Geurs, Karl.; Melbye, Lisa.; Fassett, Mucci; Twentieth Century Fox Home Entertainment, Inc.; American Greetings Corporation (Beverly Hills, Calif. : 20th Century Fox, 2009)
Life is berry sweet in Berry Bitty City where Strawberry runs the Berry Cafe. But, when Berry City's water supply is in jeopardy, Strawberry must find a way to rescue the town, and learns that when you have good friends and faith in yourself, any challenge can be overcome.
Special features: Music video "Cafe cabaret" ; sing-a-long ; DVD-ROM printable coloring pages.
Editor, Steve "Sketch" Vallino ; music, Chip Whitewood and Ashley Saunig.
Voices: Anna Cummer, Ashleigh Ball, Ingrid Nilson, Janyse Jaud, Britt McKillup, Andrea Libman, Paul Dobson.
DVD, widescreen (1.78:1), Dolby digital surround 5.1.
English or Spanish dialogue; English or Spanish subtitles; closed-captioned.
Keywords: Strawberry Shortcake (Fictitious character) -- Juvenile drama; Strawberry Shortcake (Fictitious character) -- Juvenile films; Friendship -- Juvenile films; Water-supply -- Juvenile films; Feature films; Children's films; Video recordings for the hearing impaired; French language materials; Spanish language materials